Curcumin Analog CH-5 Suppresses the Proliferation, Migration, and Invasion of the Human Gastric Cancer Cell Line HGC-27 - Silva, Gabriel; Lima, Felipe Teixeira; Seba, Viviane; Mendes Lourenco, Ana Laura; Lucas, Thaise Graminha; Andrade, Bianca Vieira de; Torrezan, Guilherme Silva [UNESP]; Polaquini, Carlos Roberto [UNESP]; Garcia, Marcelo Engracia; Couto, Lucelio Bernardes; Bestetti, Reinaldo Bulgarelli; Franca, Suzelei de Castro; et al. (Mdpi, 2018)
Gastric cancer is one of the most frequent malignant tumors in the world. The majority of patients are diagnosed with metastatic gastric cancer, which has a low survival rate. These data reinforce the importance of studying the anticancer activity of new molecules with the potential to suppress gastric cancer metastasis. Curcumin is a well-studied compound that has demonstrated anti-metastatic effects. Here we investigated if CH-5, a curcumin derivative compound, has anti-metastatic properties in the human gastric cancer cell line HGC-27. Firstly, we found that CH-5 decreased viability and induced apoptosis in HGC-27 cells in a dose-dependent manner. Additionally, CH-5 suppressed the migration and invasion of HGC-27 cells by downregulating the expression and collagenase activity of matrix metalloproteinase 2 in a dose-dependent manner. In conclusion, CH-5 showed anticancer activities, including the induction of apoptosis, and the suppression of migration and invasion in HGC-27 cells, suggesting that CH-5 can be a lead molecule for the development of anti-metastatic drugs for gastric cancer therapy.
Keywords: gastric cancer; curcumin; matrix metalloproteinase 2; migration; invasion; apoptosis